(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
These days it’s hard to find someone who hasn’t heard of Artificial Intelligence (AI). It is a reality of today’s life. Although there are many questions – how to use it effectively, especially in higher education and research. Therefore, the question of AI Literacy becomes relevant, where the key aspects relate to knowledge, skills and psychosocial factors, including a positive attitude towards AI technology and tools. In order to conduct the corresponding transformation of teaching, learning and assessment from the perspective of higher education, the readiness to use AI tools on the example of AI Chat Tools by staff must first be determined. So, within the scope of ERASMUS+ project “DialogEduShift: Transforming Higher Education Teaching and Evaluation Approaches in the Era of AI Chat Tools” the survey was created for cross-country research, including the respondents from the following countries: Poland, Germany, Turkey, Ukraine, Latvia. A comparative analysis of the survey results was then conducted regarding the perspective of three respondent groups: experts in IT field, academician, and university administration. While some questions were specified and intended only for academician. This article reviews the insights and suggestions gathered during the survey by creating the list of guidelines for effective transformation of teaching and assessment in higher education institutions in the Era of AI Chat Tools. The aim of the article is to determine the AI Literacy of three groups of respondents: IT experts, academician, and university administration who use AI Chat Tools to increase the effectiveness of their work and to summarize the guidelines for updating and renewing teaching and evaluation approaches in higher education institutions by implementing AI Chat Tools. This research is valuable for improving AI Literacy of higher education staff.